2014
DOI: 10.1002/dev.21185
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and mothering: Challenges faced by teenage mothers

Abstract: Previous research has established that in comparison to adult mothers teen mothers respond less sensitively to their infants. In adults, components of executive functions relate directly to maternal sensitivity. Since teenagers are known to have a less developed prefrontal cortex and greater difficulties in parenting, this study sought to determine whether the association between executive processes and mothering exists among teenagers. Two groups of mothers, teens (n = 30) and adults (n = 27), who were approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 45 publications
5
61
1
6
Order By: Relevance
“…In the first study to consider parent executive functioning, Deater-Deckard and colleagues (Deater-Deckard, Sewell, Petrill, & Thompson, 2010) reported that mothers with lower working memory reacted more negatively to challenging child behavior than mothers with better working memory. Subsequent work has shown that mothers with poor executive functioning are more likely to harshly respond to child conduct problems (Deater-Deckard, Wang, Chen, & Bell, 2012), and mothers with poor spatial working memory have been found to be less sensitive while interacting with their infants (Gonzalez, Jenkins, Steiner, & Fleming, 2012; also see Chico, Gonzalez, Ali, Steiner, & Fleming, 2014). Although these studies were cross-sectional, Cuevas and colleagues (2014a,b) reported longitudinal relations between better maternal executive functioning and fewer negative caregiving behaviors, with such caregiving also showing relations with children’s executive functioning at 36 and 48 months, but not at 24 months.…”
Section: Associations Between Parent and Child Self-regulationmentioning
confidence: 99%
“…In the first study to consider parent executive functioning, Deater-Deckard and colleagues (Deater-Deckard, Sewell, Petrill, & Thompson, 2010) reported that mothers with lower working memory reacted more negatively to challenging child behavior than mothers with better working memory. Subsequent work has shown that mothers with poor executive functioning are more likely to harshly respond to child conduct problems (Deater-Deckard, Wang, Chen, & Bell, 2012), and mothers with poor spatial working memory have been found to be less sensitive while interacting with their infants (Gonzalez, Jenkins, Steiner, & Fleming, 2012; also see Chico, Gonzalez, Ali, Steiner, & Fleming, 2014). Although these studies were cross-sectional, Cuevas and colleagues (2014a,b) reported longitudinal relations between better maternal executive functioning and fewer negative caregiving behaviors, with such caregiving also showing relations with children’s executive functioning at 36 and 48 months, but not at 24 months.…”
Section: Associations Between Parent and Child Self-regulationmentioning
confidence: 99%
“…Several studies explored aspects of maternal emotion and cognitive control and a range of positive parenting measures. Across the life course of childhood, higher maternal emotion control and cognitive control is associated with supportive responses to child's negative emotion (Hughes & Gullone, 2010; Valiente et al, 2007), increased maternal sensitivity and warmth (Chico, Gonzalez, Ali, Steiner, & Fleming, 2014; Gonzalez, Jenkins, Steiner, & Fleming, 2012), more affectional expression (Wietecha et al, 2012), more time spent on caregiving activities (Bridgett et al, 2011) and a higher sense of parenting confidence (Wietecha et al, 2012). On the other hand, lower maternal emotion and cognitive control is associated with less monitoring (Babinski et al, 2012; Murray & Johnston, 2006), less maternal involvement (Boutwell & Beaver, 2010; Chen & Johnston, 2007; Chronis-Tuscano, Raggi, et al, 2008; Mokrova et al, 2010), less parental satisfaction (Watkins & Mash, 2009), and less generally positive parenting (Chronis-Tuscano, Raggi, et al, 2008; Psychogiou, Daley, Thompson, & Sonuga-Barke, 2007).…”
Section: State Of the Science: Maternal Emotion And Cognitive Controlmentioning
confidence: 99%
“…But when stress does arise, it has been shown to increase distractibility and reduce working memory and attention control (Luethi et al, 2009; Lupien et al, 2009). Adolescents’ prefrontal cortex functions may be especially sensitive to the effects of stress (Lupien et al, 2009), putting adolescent parents at particular risk for impaired cognitive and emotional control functioning in high-stress situations (see Chico et al, 2014). …”
Section: Plasticity Of Emotion and Cognitive Control Capacitiesmentioning
confidence: 99%
“…This is particularly the case with teenage mothers, who tend to respond less sensitively to their infants. Teenagers in general, but teenage mothers especially, tend also to show much poorer attention, executive function, and impulse control (Chico, Gonzalez, Ali, Steiner, & Fleming, 2014; Geier, Terwilliger, Teslovich, Velanova, & Luna, 2010; McAnarney, 2008; Rubia, Hyde, Halari, Giampietro, & Smith, 2010; Sturman & Moghaddam, 2011; Van Leijenhorst et al, 2010). …”
Section: Postpartum Learning Cognition and Executive Functionmentioning
confidence: 99%